Β‐Adrenergic Stimulation Induces Histone Deacetylase 5 (HDAC5) Nuclear Accumulation in Cardiomyocytes by B55α‐PP2A‐Mediated Dephosphorylation. Issue 4 (April 2017) - Weeks, Kate L.; Ranieri, Antonella; Karaś, Agnieszka; Bernardo, Bianca C.; Ashcroft, Alexandra S.; Molenaar, Chris; McMullen, Julie R.; Avkiran, Metin
Abstract : Background: Class IIa histone deacetylase (HDAC) isoforms such as HDAC5 are critical signal‐responsive repressors of maladaptive cardiomyocyte hypertrophy, through nuclear interactions with transcription factors including myocyte enhancer factor‐2. β‐Adrenoceptor (β‐AR) stimulation, a signal of fundamental importance in regulating cardiac function, has been proposed to induce both phosphorylation‐independent nuclear export and phosphorylation‐dependent nuclear accumulation of cardiomyocyte HDAC5. The relative importance of phosphorylation at Ser259/Ser498 versus Ser279 in HDAC5 regulation is also controversial. We aimed to determine the impact of β‐AR stimulation on the phosphorylation, localization, and function of cardiomyocyte HDAC5 and delineate underlying molecular mechanisms. Methods and Results: A novel 3‐dimensional confocal microscopy method that objectively quantifies the whole‐cell nuclear/cytoplasmic distribution of green fluorescent protein tagged HDAC5 revealed the β‐AR agonist isoproterenol to induce β1 ‐AR‐mediated and protein kinase A‐dependent HDAC5 nuclear accumulation in adult rat cardiomyocytes, which was accompanied by dephosphorylation at Ser259/279/498. Mutation of Ser259/Ser498 to Ala promoted HDAC5 nuclear accumulation and myocyte enhancer factor‐2 inhibition, whereas Ser279 ablation had no such effect and did not block isoproterenol‐induced nuclear accumulation. Inhibition of the Ser/Thr phosphatase PP2A blocked isoproterenol‐induced HDAC5 dephosphorylation. Co‐immunoprecipitation revealed a specific interaction of HDAC5 with the PP2A targeting subunit B55α, as well as catalytic and scaffolding subunits, which increased >3‐fold with isoproterenol. Knockdown of B55α in neonatal cardiomyocytes attenuated isoproterenol‐induced HDAC5 dephosphorylation. Conclusions: β‐AR stimulation induces HDAC5 nuclear accumulation in cardiomyocytes by a mechanism that is protein kinase A‐dependent but requires B55α‐PP2A‐mediated dephosphorylation of Ser259/Ser498 rather than protein kinase A‐mediated phosphorylation of Ser279.